Trajetórias da bovinocultura de corte no Brasil e no estado de Goiás: perspectivas para uma transição sustentável - Gomes, Raquel Oliveira (2023)
The dissertation is presented in the format of two articles. The first article sought to understand the elements linked to the economic and environmental issue in relation to the characteristics of beef cattle in Brazil and in the state of Goiás, investigating the advances in the main areas highlighted by the literature on the subject, mainly in the issue of animal food quality and in the implementation of integrated systems. The results show that for advances to be achieved in the environmental area, it is necessary that the alternatives presented to the producers consider their economic attractiveness and the operational capacity of their implementation. The second article sought to investigate the effects of demand and supply shocks on the trajectories of beef cattle in Brazil and the state of Goiás, taking into account the environmental aspect. Theoretically, we sought to include greenhouse gas emissions in the econometric modeling of a structural VAR, building on the traditional models initiated by Blanchard and Quah (1989) for Brazilian beef cattle. In the first article, it was possible to identify a set of advances in supplementation and confinement practices that have the potential to reduce greenhouse gases produced by beef cattle. However, the adoption of integrated systems by producers has not yet been shown to be a chosen alternative. In the second article, it was mainly observed that there is a need for planning the growth of the herds at a national level and in the state of Goiás, so that the increase in production in the coming years takes place with productivity gains and a reduction of the environmental impacts of the sector. In general, the components of GHG emissions, which also represent the sector's technological standard, and animal stock had the greatest long-term impacts on the other variables in the sector, reinforcing the need to combine good production practices to increase productivity and reduce the sector's impacts on the environment.